2004
DOI: 10.2460/javma.2004.224.717
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic findings in dogs with hyperammonemia: 90 cases (2000–2002)

Abstract: Objective—To determine ultrasonographic abnormalities in dogs with hyperammonemia. Design—Retrospective study. Animals—90 client-owned dogs with hyperammonemia. Procedure—Ultrasonography of the abdominal vessels and organs was performed in a systematic way. Dogs in which the ultrasonographic diagnosis was a congenital portosystemic shunt were included only if they underwent laparotomy or necropsy. Dogs in which the abdominal vasculature appeared normal and dogs in which the ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 40 publications
3
82
0
Order By: Relevance
“…http://www.openveterinaryjournal.com M. Ricciardi Open Veterinary Journal, (2017 On the other hand patients with congenital PSS are traditionally described as having a single porto-caval connection without ascites or portal flow obstruction (Szatmari et al, 2004;Bertolini et al, 2006;Nelson and Nelson, 2011;Fukushima et al, 2014). Furthermore, current classification of canine PSS differentiate repeatable and distinct vascular patterns of CPSS and APSS without any overlapping of anatomical pathway between each category (Ricciardi, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…http://www.openveterinaryjournal.com M. Ricciardi Open Veterinary Journal, (2017 On the other hand patients with congenital PSS are traditionally described as having a single porto-caval connection without ascites or portal flow obstruction (Szatmari et al, 2004;Bertolini et al, 2006;Nelson and Nelson, 2011;Fukushima et al, 2014). Furthermore, current classification of canine PSS differentiate repeatable and distinct vascular patterns of CPSS and APSS without any overlapping of anatomical pathway between each category (Ricciardi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These vascular anomalies are divided in two main categories according to their origin: congenital PSS (CPSS) deriving from embryogenetic errors in the development of vitelline and cardinal venous systems (Ferrell et al, 2003), and acquired PSS (APSS) deriving from recanalization of pre-existing, vestigial embryonic vascular connections between portal and caval systems as a consequence of portal hypertension (PH) (Fossum, 2002;Szatmari et al, 2004;Bertolini, 2010a). Ultrasound and computed tomography (CT) are reliable imaging techniques for the non-invasive diagnosis of PSSs and for distinction between acquired and congenital shunts (Szatmari and Rothuizen, 2002;Szatmari et al, 2004;Ricciardi, 2016). Such imaging distinction is essential for differentiating hypertensive patients, which need further investigations in order to diagnose the cause of the underlying PH, from those that need surgical closure of a congenital vascular malformation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in our experience, congenital extrahepatic spleniccaval shunts seem to be surrounded by liver when they are scanned via a right intercostal approach. In a study 16 of 90 dogs with hyperammonemia, we found that the present protocol for systematic ultrasonographic evaluation of the portal system was effective in identifying CPSSs and APSSs and ruling out portosystemic shunting in dogs with urea cycle enzyme deficiencies. In our experience, however, high accuracy also required that in addition to use of the scanning protocol, a high-quality ultrasound machine with excellent gray scale resolution was needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that in 2 of these studies, some extrahepatic CPSS were not recognized because only a right intercostal approach was used. For example, in a study 16 of 90 dogs with hyperammonemia secondary to CPSSs, APSSs, or urea cycle enzyme deficiency, we found that congenital extrahepatic right gastric-caval shunts cannot be readily identified from a right intercostal approach because visualization of the Figure 2-Ultrasonogram of the abdomen of a healthy male adult Beagle. The dog was in left lateral recumbency, and the transducer was oriented transversely and placed in a more cranial right intercostal space, compared with the orientation in Figure 1 (plane 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation